Consumer Preference Analysis in Choosing Coffee Shops in Semarang Using Conjoint Analysis - Lisa Qotrunnada; Naniek Utami Handayani; M. Mujiya Ulkhaq (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2025)
The trend of drinking coffee at coffee shops is becoming increasingly popular in Indonesia, especially in Semarang, where there are now numerous coffee shops. With so many options available, consumers often face difficulty choosing a café, while coffee shop owners want to understand consumer preferences regarding aspects such as beverage products, affordable pricing, café ambiance, service quality, strategic location, and comprehensive facilities. This study aims to identify the ranking of consumer preferences for the combination and levels of attributes when choosing a café in Semarang. The study uses conjoint analysis, involving 96 respondents who have visited cafés in Semarang. Data were collected using purposive sampling. The study focuses on six attributes: product, price, café ambiance, service, location, and facilities, each with three levels. The results indicate the preferred combination and levels of attributes for consumers, which include: a price range of Rp. 10,000 – Rp. 15,000, a semi-outdoor café ambiance, visually appealing menu items, wifi facilities, a location close to residents, and very fast service.